Complex Formation between the Transcription Factor WRKY53 and Antioxidative Enzymes Leads to Reciprocal Inhibition - Ana Gabriela Andrade Galan; Jasmin Doll; Natalie Faiß; Patricia Weber; Ulrike Zentgraf (MDPI AG, 2024)
The transcription factor WRKY53 of the model plant Arabidopsis thaliana is an important regulator of leaf senescence. Its expression, activity and degradation are tightly controlled by various mechanisms and feedback loops. Hydrogen peroxide is one of the inducing agents for WRKY53 expression, and a long-lasting intracellular increase in H2O2 content accompanies the upregulation of WRKY53 at the onset of leaf senescence. We have identified different antioxidative enzymes, including catalases (CATs), superoxide dismutases (SODs) and ascorbate peroxidases (APXs), as protein interaction partners of WRKY53 in a WRKY53-pulldown experiment at different developmental stages. The interaction of WRKY53 with these enzymes was confirmed in vivo by bimolecular fluorescence complementation assays (BiFC) in Arabidopsis protoplasts and transiently transformed tobacco leaves. The interaction with WRKY53 inhibited the activity of the enzyme isoforms CAT2, CAT3, APX1, Cu/ZuSOD1 and FeSOD1 (and vice versa), while the function of WRKY53 as a transcription factor was also inhibited by these complex formations. Other WRKY factors like WRKY18 or WRKY25 had no or only mild inhibitory effects on the enzyme activities, indicating that WRKY53 has a central position in this crosstalk. Taken together, we identified a new additional and unexpected feedback regulation between H2O2, the antioxidative enzymes and the transcription factor WRKY53.